Multi-Objective Design of a Pneumatic Adaptive Impact Absorber - WISZOWATY, Rafal; GRACZYKOWSKI, Cezary; MIKUŁOWSKI, Grzegorz; HOLNICKI-SZULC, Jan; WOŁEJSZA, Zbigniew; ORŁOWSKA-GAŁĘZIA, Anita; JANKOWSKI, Łukasz (Engineering Transactions, 2025)
This manuscript proposes a multicriteria approach to the design optimization of adaptive pneumatic impact absorbers. The considered absorber consists of two sealed chambers separated by a piston with an internal valve. Proper valve control affects gas flow between the chambers and ensures a flat reaction force profile over a possibly long piston stroke. The design of such an absorber is defined by three parameters: initial gas pressure, diameter, and length. For a given range of impact conditions, the worst-case maximum deceleration and maximum mass flow rate are used as design criteria in a multicriterial minimization problem. Solutions to this problem provide an optimal balance between impact absorption performance and the technical requirements the valve must meet. An example is considered, which illustrates the Pareto-optimal solutions in the design space and the complex interdependency between initial pressure and absorber diameter at each absorber length. The results demonstrate that a proper choice of design parameters can result in significant performance improvements.